Investigation on shear strength of stabilised clay using cement, sodium silicate and slag - Vakili, M.; Chegenizadeh, Amin; Nikraz, Hamid; Keramatikerman, M. (Elsevier BV, 2016)
© 2016 Elsevier B.V. A total number of 84 direct shear tests (DST) were performed on slag, sodium silicate, and cemented clay compositions to determine how these materials affect the engineering properties of cemented clay. A constant 2% percentage (by weight) of cement in clay with three different ratios of sodium silicate (1%, 1.5% and 2.5% by weight of dry soil) were mixed with three different percentages of slag (3%, 4% and 5% by weight of dry soil) and tested based on curing times of 7, 14 and 28. days under three types of vertical load, being 50. kPa, 150. kPa and 250. kPa respectively. The results indicated that the shear resistance of cured cemented clay soil was improved by adding percentages of slag and sodium silicate, and this improvement was almost three times stronger for the third sample (1% sodium silicate and 5% slag) under a 250. kPa normal load compared with untreated soil, however sodium silicate generally showed a reverse effect on the improvement of soil shear resistance properties. Observing the visual characteristics using micrographs and X-ray diffraction patterns from the ultimate composition and each component by SEM/EDS and XRD phase analysis techniques, confirmed this improvement in shear resistance.